The effect of Fe2NiO4 and Fe4NiO4Zn magnetic nanoparticles on anaerobic digestion activity - Chen, Jian Lin (2020)
Two types of magnetic nanoparticles (MNPs), i.e. Ni ferrite nanoparticles (Fe2NiO4) and Ni Zn ferrite nanoparticles (Fe4NiO4Zn) containing the trace metals Ni and Fe, were added to the anaerobic digestion of synthetic municipal wastewater at concentrations between 1 and 100 mg Ni L-1 in order to compare their effects on biogas (methane) production and sludge activity. Using the production of methane over time as a measure, the assays revealed that anaerobic digestion was stimulated by the addition of 100 mg Ni L-1 in Fe2NiO4 NPs, while it was inhibited by the addition of 1-100 mg Ni L-1 in Fe4NiO4Zn NPs. Especially at 100 mg Ni L-1, Fe4NiO4Zn NPs resulted in a total inhibition of anaerobic digestion. The metabolic activity of the anaerobic sludge was tested using the resazurin reduction assay, and the assay clearly revealed the negative effect of Fe4NiO4Zn NPs and the positive effect of Fe2NiO4 NPs. Re-feeding fresh synthetic medium reactivated the NPs added to the anaerobic sludge, except for the experiment with 100 mg Ni L-1 addition of Fe4NiO4Zn NPs. The findings in this present study indicate a possible new strategy for NPs design to enhance anaerobic digestion.